Responsivitas Pelayanan Publik Di Rumah Tahanan Negara Kelas Ii B Enrekang - Fitriani, Fitriani; Mahsyar, Abdul; Rasdiana, Rasdiana (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study aims to determine whether the provision of services was in accordance with the Standard Operational Procedure (SOP) seen from how the ability to respond and respond to complaints, how the speed, accuracy and timeliness of service delivery. This research used quantitative methods to describe the responsiveness of public services specifically about coaching. The sample was 10% of employees who were selected by simple random sampling from 20% of the population. The research data was collected using instruments in the form of questionnaires, interviews and documentation. The results showed that the guidance services at the Enrekang Regency State Detention Center,were good, this was based on the descriptive results of the percentage that the implementation of prison services was in accordance with the Standard Operational Procedure (SOP). However, the results of interviews from service officers indicated that the prisoners were late in understanding any information provided, especially in providing guidance services, was still very low due to the limited number of officers compared to the number of prisoners.  Keywords: Responsiveness, Class II B Prison EnrekangABSTRACTThis study aims to determine whether the provision of services was in accordance with the Standard Operational Procedure (SOP) seen from how the ability to respond and respond to complaints, how the speed, accuracy and timeliness of service delivery. This research used quantitative methods to describe the responsiveness of public services specifically about coaching. The sample was 10% of employees who were selected by simple random sampling from 20% of the population. The research data was collected using instruments in the form of questionnaires, interviews and documentation. The results showed that the guidance services at the Enrekang Regency State Detention Center,were good, this was based on the descriptive results of the percentage that the implementation of prison services was in accordance with the Standard Operational Procedure (SOP). However, the results of interviews from service officers indicated that the prisoners were late in understanding any information provided, especially in providing guidance services, was still very low due to the limited number of officers compared to the number of prisoners.  Keywords: Responsiveness, Class II B Prison Enrekang